The role of oxidative and inflammatory stress and persistent viral infections in immunosenescence. (September 2016) - Bauer, Moisés Evandro; Fuente, Mónica De la
Highlights: Human cytomegalovirus (CMV) promotes immunosenescence by targeting T cells. The oxidation-inflammation leads to age-related decline of physiological functions. The immunosenescence is involved in the rate of ageing of individuals. Abstract: Immunosenescence involves age-related remodeling changes in the organization of lymphoid organs and functionality of immune cells, which have been associated with increased morbidity and mortality The pace of immunosenescence is modulated, however, by both intrinsic and extrinsic factors. Here, we review the mechanisms by which some factors, like the oxidative stress and certain chronic viral infections, may modulate the ageing immune system. Mounting evidence indicates that human cytomegalovirus (CMV) drives the expansion of late-differentiated T cells with an inflammatory profile. This would add to the "inflammaging" phenomenon, characterized by a low-grade inflammatory state, importantly involved in the etiology of several age-related diseases. We discuss that age-related oxidative stress is associated with chronic inflammation, and the oxidation-inflammation theory of ageing is summarized. According to this theory, the ageing process is a chronic oxidative and inflammatory stress, leading to damage of cell components, including proteins, lipids and DNA, and contributing to the age-related decline of physiological functions. Moreover oxi-inflamm-aging is associated with immunosenescence, which could be involved in the rate of ageing of individuals.